Reconstructing Qur’anic Meaning Through Intertextual Polysemy: Abdulla Galadari’s Hermeneutical Implications for Contemporary Tafsir - Tria Feri Ardona (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
Contemporary Qur’anic interpretation continues to face an enduring tension between classical exegetical authority and emerging modern hermeneutical approaches. In increasingly plural and interconnected religious societies, contemporary tafsir requires interpretive frameworks capable of engaging both the internal linguistic dimensions of the Qur’an and its broader interreligious textual environment. However, despite the growing development of contextual tafsir studies, the hermeneutical potential of intertextual approaches - particularly those involving scriptural traditions beyond the Qur’an - remains insufficiently explored within contemporary Islamic studies discourse. This paper examines the hermeneutical implications of Abdulla Galadari’s theory of intertextual polysemy for contemporary Qur’anic interpretation. It seeks to position Galadari’s approach within broader debates surrounding contextual tafsir, interreligious textuality, and modern Qur’anic hermeneutics. Using a qualitative library research methodology, this study analyzes Galadari’s major works, particularly his article on intertextual polysemy (2013) and his monograph Qur’anic Hermeneutics: Between Science, History, and the Bible (2018), alongside comparative hermeneutical perspectives drawn from Julia Kristeva, Michael Fishbane, and Gabriel Said Reynolds. This study argues that Galadari’s intertextual polysemy offers a distinctive hermeneutical model in contemporary tafsir by integrating semantic analysis of Arabic root structures with intertextual engagements involving Biblical and Rabbinic traditions. Rather than reducing the Qur’an to a merely historical text or limiting interpretation within rigid exegetical boundaries, this approach expands the interpretive possibilities embedded within the Qur’an’s linguistic and textual architecture. In doing so, Galadari proposes an alternative interpretive pathway that maintains the theological authority of the Qur’an while simultaneously opening broader dialogical and contextual horizons of meaning. The findings demonstrate that intertextual polysemy provides important hermeneutical resources for the development of contextual tafsir in religiously plural societies, particularly within the contemporary Southeast Asian Muslim intellectual context.